UJI EFEKTIVITAS ANTI BAKTERI EKSTRAK DAUN LEUNCA (SOLANUM NIGRUM) TERHADAP DAYA HAMBAT BAKTERI ESCHERICHIA COLI - Fahdi, Firdaus; Sari, Herviani; Saulina Lubis, Lisbet (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2020)
Antibacterial is a compound that can inhibit the growth of bacteria that can be used for the treatment of infections in humans. One of the bacteria that can cause interference with the system is the Escherichia coli bacteria, where the Escherichia coli bacteria is widely spread around us. The spread of the Escherichia coli bacteria can occur by direct contact (shaking hands, touching). Then passed on by mouth. Leunca leaves have chemical contents including alkaloids, flavonoids, saponins, tanins. The purpose of this study was to determine whether Leunca's leaf extract (Solanum nigrum) has antibacterial effects against the inhibitory power of Escherichia coli bacteria with a concentration of 50 mg/ml, 100 mg/ml, 150 mg/ml, 200 mg/ml, 250 mg/ml. The method of this study was the sample of Leunca leaf obtained from West Lumban Rau Village, Habinsaran Subdistrict, Toba Samosir Regency. Sample preparation was done by making thick extract with the maceration method. An anti-bacterial effectiveness test is done by the disk diffusion method. The results showed Leunca's leaf extract containing alkaloid compounds, flavonoids, saponins, tannins. As well as having antibacterial effectiveness against the inhibition of Escherichia coli bacteria. Average inhibition zone area concentration of 50 mg/ml = 6.1 mm, concentration of 100 mg/ml = 7.3, concentration of 150 mg/ml = 8.8 mm, concentration of 200 mg/ml = 10.8 mm, concentration of 250 mg/ml = 12.6 mm. Conclusion: Leunca (Solanum nigrum) Leaf Extract has antibacterial effects against the inhibitory power of Escherichia coli bacteria with a strong category.